3/4 - 3/2 + (2 1/2 - 1 7/8) * 8- 2 1/4 = 2
Ja robiłam to tak :
3/4 - 3/2 + ( 2 1/2 - 1 7/8) * 8- 2 1/4 =3/4 - 6/4 + +( 5/2 - 15/8) * 8 - - 2 1/4 = 3/4 - 6/4 + ( 20/8 - -15/8 )* 8 - 2 1/4 = 3/4 - 6/4 + 5/8 * 8 -2 1/4 = =3/4 - 6/4 + 5 - 2 1/4 = i tu się pogubiłam

3

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-05T13:23:18+02:00
3/4-3/2+(2 1/2- 1 7/8) * 8- 2 1/4 =
= 3/4-6/4+(2 4/8-1 7/8)*8-9/4=
=3/4-6/4+(20/8-15/8)*8-9/4=
=-3/4+(5/8)*8-9/4=
=-3/4+5-9/4=
=-3/4+20/4-9/4=
=17/4-9/4=
=8/4=2
pozdrawiam
dagmara
2009-09-05T13:28:20+02:00
¾ - 3/2 + (2 ½ - 1 7/8) * 8- 2 ¼ =
¾ - 6/4 + (2 4/8 - 1 7/8) * 8 - 2 ¼ =
-¾ + (20/8 - 15/8) * 8 - 2 ¼ =
-¾ + 5/8 * 8 - 2 ¼ =
-3 + 5 = 2
2009-09-05T14:13:22+02:00
3/4 - 3/2 + (2 1/2 - 1 7/8) * 8- 2 1/4

3/4 - 6/4 + 20-15 - 9/4 = 5-12/4=5-3=2